PERLINDUNGAN HUKUM BAGI ISTRI KORBAN KEKERASAN DALAM RUMAH TANGGA PADA PUTUSAN PERCERAIAN MAHKAMAH AGUNG - Saeroni (LP3M IAI Al-Qolam, 2020)
This study aims to know and analys the legal protection for wife as survivor of domestic violence (DV) in the divorce verdicts of Supreme Court within Religious Court jurisdiction on the perspective Supreme Court Chairmen Decree Number KMA/032/SK/IV/2006 on The Application of 2nd Book: The Guidelines for the Task Implementation and Administration of Religious Court and the feminist legal theory. It is juridical normative research that reviews the legal norms, regulations and verdicts of the Supreme Court on the cases of divorce for reasons of domestic violence (DV) within the Religious Courts jurisdiction in 2011 to 2013. The analysis is conducted qualitatively by synchronizing between the material and the legal norms which are being studied with the legal norms in KMA/032/SK/IV/2006 and the legal theories based on the ideas of feminist legal theory. The results of this research shows that the legal protection for wife as survivor of DV in the divorce virdicts of Supreme Court have not been in line with the Supreme Court Chairmen Decree No. KMA/032/SK/IV/2006 on TheApplication of 2nd Book: The Guidelines for the Task Implementation and Administration of Religion Court. There are no one of the Supreme Court virdicts has considered DVA to decide divorce casescaused by domestic violence and no one has used the ex-officio authority of judge to decide nafkah iddahin contested divorce cases because of domestic violence. According to the feminist legal theory the divorce verdicts of Supreme Court have not given enough legal protection for wife as survivor of domestic violence. That is because of the verdicts of Supreme Court have not complied feeling justice of wife as survivor of domestic violence to get nafkah iddah and mut’ah on the contested divorce cases.